Multiply the first and last term (6x² * -4) to get -24x². Now find two factors of -24x² whose sum is the middle term (5x). -<em>3x + 8x </em>Replace 5x with -3x + 8x, then factor and solve.
6x² - 3x + 8x - 4 = 0
3x(<u>2x - 1</u>) +4(<u>2x - 1</u>) = 0
(3x + 4) (<u>2x - 1</u>) = 0
3x + 4 = 0 or 2x - 1 = 0
x = or x =
<em>Note: you can also use the quadratic formula to find the foots.</em>
The error is that 9 shouldnt be written as nine it should be written as 3x3 or 3^2. So the answer should be 2^3 x 3^2 because 9 can be divided into even more prime factors of 72.